Construction Defect and Maintenance Problem of Watering Apparatus and Sanitary Work in Apartment Building - Deokseok Seo, Junmo Park (International Journal of Advanced Science and Technology, 2020)
There are disputes between the producer and consumers because there are problems on the building due to various causes. The disputes related with the construction defect occurred on the apartment building which is most general type of apartment in Korea. Natural deterioration of the watering apparatus and sanitary facility among various facilities composing the apartment building is progressed relatively soon because it uses the water. Representatively, there can sbe increasing of financial damage as well as the inconvenience of the resident when there is a problem such as water leak, pipe corrosion and so on. However, the dispute expanded as lawsuit because it is difficult to classify clearly that the problems are by the mistake during the construction such as design and building or by insufficient maintenance or natural deterioration. I compared the defect occurred on watering apparatus and sanitary facility of apartment building relatively in terms of construction and maintenance. To do this, I checked for the difference for each item designated by relative regulations. Then, I interpreted the trend of defect actually occurred in the apartment house for last 10 years according to each point of view. I looked the alternative for systematic maintenance of watering apparatus and sanitary facility based on it. Based on the review for current regulations, the point of view in the construction and maintenance for the defect is different in general. Maximum ten years of reliability is forced as term of defect warranty liability and 3% of total construction cost as defect repairing bond to the project entity from the point of view of construction. However, the regulation recommends the management for maximum thirty years to the person holding a partitioned ownership and gathers relatively low level of long-term maintenance cost from the point of view of maintenance. There is one-year difference because the term of defect warranty liability is two years while the time exceeding 95% of cumulative rate of occurred defects is three years when examine actually occurred problems from the point of view of construction defect. So, the term of defect warranty liability should be adjusted as three years to protect the person holding a partitioned ownership from the point of view of construction defect. Also, it is expected to help on the life cycle management if the problems occurred initially are properly repaired in terms of ten years of replacement cycle of pump and pipe mainly occurred the problem and most of the problem occurred in watering apparatus and sanitary work occurred within five years which is initial stage of life cycle when examine from the point of view of maintenance. Meanwhile, the lawsuit for the defect on the apartment is mainly raised at the time passing three years to five years after the completion of construction, so the construction defect for maximum ten years including the reliability of project entity in the regulation can be settled. However, the problems after it should be managed and repaired absolutely under the reliability of the user. However, there should be more practical management plan should be prepared because current long-term maintenance plan only emphasizes comprehensive and long-term point of view, but the management requirements are not specific, and especially, there is lack of base for standard on the repair and replacement time designated without variation because it is very much influenced according to the use in the facilities such as watering apparatus and sanitary work. Accordingly, necessary supplementation and the item to be researched are limited for the initial, midterm and long-term stage in this research. In the initial stage, there should be the standard classifying the reliability with clear classification because there is mixing of construction defect and maintenance problem. In the midterm stage, long-term maintenance plan specialized to relative apartment building complex is necessary and the guideline with repair method for practical affairs should be developed. For the long term, renew long-term maintenance plan continuously with the analysis for the observation and management record for last ten years and develop standardized maintenance plan based on it and reflect it in the initial plan establishment of new complex (considering from design to construction).